Industrial Labor Social Movement against the Issue of Neoliberalism (Case Study on the Movement and View of Trade Unions in Indonesia on the Global Issue of Neoliberalism) - Yudhi Rachman; Bangun Sentosa DH (IPTEK Journal of Proceedings Series, 2019)
In December 1999, there was a large demonstration in Seattle, United States which triggered large demonstrations elsewhere to oppose neo-liberalism. An ideology of the capitalists in uniting a world economy free of national boundaries. Neoliberalism policies also occur in Indonesia, such as through privatization, the application of a flexible labor market or outsourcing The problem discussed in this paper is how the trade union movement and response to the policy of neoliberalism theoretical studies in this study use Marx's Conflict Theory, Smelserian social movements and Gramsci's Hegemony. This research uses descriptive, qualitative type The results showed that there were two types of trade unions that emerged after the reform, namely moderate trade unions and radical trade unions. The responses of these two types of trade unions differ in their response to the policy of neoliberalism. The first union prefers compromise while the radical trade union prefers confrontational methods. The emergence of labor awareness about the dangers of neoliberalism is a step forward when compared to the image of the previous labor movement. which only moves at the level of normative issues